(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This article presents a process of asset-backed securities of receivables , from the point of view of a company, the initiator of the process. Asset-backed securities is amethod of the company refinancing based on the use of assets. It can be carried out in the traditional or synthetic form. The article defines both forms of refinancing and presents the influence of each of them on the company’s rating.Conditions of asset-backed securities have been discussed as well as costs of such a process of refinancing. In conclusion advantages and disadvantages of true refinancing for the initiator have been presented.